A mixed‐methods study of barriers and facilitators to the implementation of postpartum hemorrhage guidelines in Uganda. Issue 1 (28th September 2015) - Braddick, Louise; Tuckey, Victoria; Abbas, Zan; Lissauer, David; Ismail, Khaled; Manaseki‐Holland, Semira; Ditai, James; Stokes, Tim
Abstract: Objective: To determine the level of adherence to postpartum hemorrhage clinical guideline recommendations and to explore context‐specific barriers and facilitators to evidence‐based obstetric care. Methods: Using direct observation of deliveries at a Ugandan healthcare facility, a mixed‐methods study was conducted between February and March 2014 to document practices related to the active management of the third stage of labor (AMTSL). The degree to which practice concurred with WHO postpartum hemorrhage guidelines was determined. Semi‐structured interviews were conducted with maternal healthcare practitioners. Results: Of 154 women, individual AMTSL, in the form of administering a uterotonic during the third stage of labor, controlled cord traction, or delayed cord clamping, occurred in 105 (68.2%), 119 (77.3%), and, of a subset of 60 patients, 37 (61.7%) individuals, respectively. However, only 18 of 53 (34.0%) individuals observed for receipt of all of the three AMTSL components received all of the essential elements of AMTSL. Three major themes influencing the uptake of evidence‐based practice were identified through 18 interviews: healthcare system issues; current knowledge, awareness, and use of clinical guidelines; and healthcare practitioner attitudes to updating their clinical practice. Conclusion: Overall guideline adherence was low. There is a need to address context‐specific barriers to uptake, ensuring guideline implementation to reduce maternal mortality in low‐resource settings.